Bacterial leakage and marginal adaptation of three bioceramics pulp dressing material - Siddiqua, Snigdha Niher Tabassum (2023)
This study aims to evaluate the sealing ability and marginal adaptation of three different bioceramics pulp dressing materials using a bacterial leakage test and scanning electron microscope (SEM). Fifty-five recently extracted lower first premolars were randomly divided into five groups, with three experimental groups (n=15), a positive control group (n=5) and a negative control group (n=5). The samples were instrumented with a modified coronal pulpotomy procedure except for the negative control group (n=5). Different types of bioceramics dressing material were placed in the cavity 3mm thickness in group 1 (Biodentine), group 2 (MTA) and group 3 (ProRoot MTA). There was no dressing material placed in the positive control group. Samples were placed in an incubator at 37℃, 100% humidity, for 24 hours to allow the material to be set, after the placement of the composite restoration. Two layers of nail varnish were applied, and the 3mm root tip was removed. The bacterial leakage test was performed using Enterococcus faecalis, and one sample from each experimental group was sliced and examined under SEM for marginal adaptation. Data analysis was conducted under the One-way ANOVA test, completed by Tukey’s post hoc test. The groups observed a significant difference in sealing ability and marginal adaptation (p<0.05), wherein Biodentine showed bacterial leakage on day 6 (7%), and on day 14 (80%), MTA showed on day 9 (14%) and on day 14 (40%), ProRoot showed on day 11 (7%) and on day 14 (33%). From SEM, ProRoot MTA demonstrated the least gap between the dressing material and significantly higher penetration in dentinal tubules. ProRoot MTA demonstrated better sealing ability and marginal adaptation compared to other groups. The finding indicates that ProRoot MTA would be the best pulp dressing material for the clinical setting. Keywords: Bacterial leakage test, bioceramics, Biodentine, MTA, ProRoot MTA, Pulpotomy, SEM.